Field trial of leaf powder of Peltophorum pterocarpum against golden apple snail in rice. - Suryanto, Edi; Ali, Jambari; Sajap, Ahmad Said; Ahmad, Faujan
The efficacy of dry leaf powder of the yellow flame tree, Peltophorum pterocarpum (Leguminosae), against the golden apple snail was evaluated in the rice field. Dosage of 0, 30, 60, 120, 180 g/4 m2 of yellow flame powder were introduced into plots with known number of snails. The dose of 30 g/4 m2 (75kg/ha) killed up to 50% of the snails within 24 hours. The dose of 60g/4 m2 or 150kg/ha killed 100% of snails within 48 hours. The yellow flame powder was readily degraded. The effect lasted only 3 days after application and fish introduced after this were not affected. It was also observed that some non-target organisms such aquatic insects are not affected by the leaf powder of the yellow flame tree. However, further investigation is warranted to study its effect on other aquatic community. The yellow flame tree then can be considered as a potential plant molluscicide.